CHARACTERIZATION OF MECHANICAL, THERMAL, AND PHYSICAL PROPERTIES OF POLYPROPYLENE COMPOSITES WITH RICE HUSK FILLER USING COUPLING AGENT MALEIC ANHYDRIDE - Santoso, Teguh Budi; Aryanti, Fitria Ika; Sitanggang, Theresia Debby Aprilia (Jurnal Teknologi Kimia Unimal, 2023)
Polypropylene is a thermoplastic that is widely applied in various automotive industries. Polypropylene is used as a matrix in composite manufacturing because it has the advantages of ease of processing, corrosion resistance, mechanical stiffness, low density, and affordable prices. The advantages of organic fillers (rice husk) are environmentally friendly, low density, and renewable. However, there is a weakness of polypropylene composites using rice husk filler, namely the lack of compatibility between the Polypropylene matrix which is hydrophobic while the filler (rice husk) is hydrophilic, to increase the bond between the matrix and filler can be done by adding a coupling agent. Based on this description, it is necessary to study the effect of the addition of maleic anhydride composition on the manufacture of polypropylene composites with rice husk filler because it can be used as an alternative in reducing agricultural waste. The addition of maleic anhydride in this study is expected to increase the bond compatibility between polypropylene and rice husk to improve the mechanical properties and crystallinity of the resulting polymer composite. The variation of this research is the composition variation (weight %) of polypropylene, rice husk, and maleic anhydride of 80:20:0, 80:18:2, 80:17:3, 80:15:5. The method used in this research is using a twin-screw extruder tool with a temperature of 190°C and then testing mechanical properties using tensile tests, thermal properties using Differential Scanning Calorimetry (DSC), and physical properties using density kits. The results showed that the mechanical properties and thermal properties of the composite increased and decreased along with the variation of maleic anhydride addition, with the highest value obtained in the variation of polypropylene, rice husk, and maleic anhydride = 80:17:3 with a tensile strength value of 10.117 MPa and a crystallinity value of 27.39%. The average density obtained for all MA additions is 0.9970 g/cm3.